2012
DOI: 10.4081/rr.2012.e6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular function by tissue Doppler imaging in patients with ankylosing spondylitis

Abstract: Ankylosing spondylitis (ASp) is a chronic, inflammatory and systemic disease affecting pericardium, myocardium and the conduction system of the heart. In this study, we aimed to analyse left ventricular systolic and diastolic functions using tissue Doppler imaging (TDI). 30 patients with ASp and 30 healthy volunteers having the similar demographic characteristics were included. Left ventricular systolic and diastolic functions were assessed by using two dimensional (2D) echocardiography, M-mode, pulsed-wave (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Histopathologic examination of myocardium in patients with AS showed that there was an increase in cells of connective tissue, particularly in reticulin fibers . Although studies on left ventricular systolic function have contradictory results, diastolic dysfunction has been shown in various studies . It is confirmed that diastolic function of patients with AS diminishes after the fifteenth year of the disease, more than systolic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic examination of myocardium in patients with AS showed that there was an increase in cells of connective tissue, particularly in reticulin fibers . Although studies on left ventricular systolic function have contradictory results, diastolic dysfunction has been shown in various studies . It is confirmed that diastolic function of patients with AS diminishes after the fifteenth year of the disease, more than systolic functions.…”
Section: Discussionmentioning
confidence: 99%